(untitled) (مجلة الرازي الطبية, 2025)
This study was conducted at Baquba Teaching Hospital and Consulting Clinic from June 2024 to August 2024, due to the importance of Pseudomonas aeruginosa bacteria that are and cause various clinical infections The study included collecting 88 samples of burn infections, wounds, ear infections, and urinary tract infections from 54.54% males (48) and 45.45% females (40). Their ages ranged from 10 to 60 years from patients hospitalized and not hospitalized the disease models were grown on MacConkey solid medium, blood medium, and Pseudomonas solid medium, and the phenotypic characteristics of the colonies were observed. Standard bacterial and biochemical tests were performed to diagnose the bacterial isolates, which included oxidase and catalase tests 10 bacterial isolates were isolated from both sexes and different ages. The percentage of isolates was of the males, 54.54% and of the females, 45.45%. The rate of diagnosis of Pseudomonas aeruginosa isolates using the VITEK2 device was 100% and the percentage of isolates from infections was Burns, ears, urinary tract, and wounds 35%, 10%, 20%,23%, respectively The isolates underwent identification and antimicrobial susceptibility testing by means of VITEK® 2 compact system Efflux pumps have a significant function in mediating antibiotic resistance in P. aeruginosa isolates The correlation between phenotypic and genotypic results, particularly the prevalence of MexA gene, underscores the importance of efflux pumps in MDR in P. aeruginosa strains from this clinical setting P. aeruginosa presents a significant clinical issue owing to its multidrug-resistant (MDR) phenotypic, resulting in severe and potentially fatal infections.